Implementasi Pendekatan Etnomatematika dalam Pembelajaran Matematika di MTs Darussalam Krempyang - Amin, Sohibul; Zalekha, Siti; Slamet, Slamet (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
Mathematics has an important role in shaping logical and systematic thinking patterns, but many students still have difficulty in understanding it. One of the reasons is the learning approach that is less contextualised, making it difficult for students to connect mathematical concepts with everyday life. Therefore, the ethnomathematics approach, which links mathematics with local culture, is a potential alternative to improve students’ understanding. This study aims to explore the application of ethnomathematics in mathematics learning at MTs Darussalam Krempyang and analyse its effectiveness in improving students’ understanding and interest in learning. This study used the Classroom Action Research (PTK) method in two cycles, with the research subjects as many as 32 students of class VIII. Data were collected through observation, interviews, questionnaires, and comprehension tests before and after the intervention. The results showed that the ethnomathematics approach significantly improved students’ understanding and learning motivation. They were more enthusiastic in participating in learning, active in discussions, and more easily understood mathematical concepts through cultural contexts, such as batik patterns and traditional measurement systems. Thus, ethnomathematics can be an innovative learning strategy that is more contextualised and meaningful to students.